2016
DOI: 10.1538/expanim.16-0028
|View full text |Cite
|
Sign up to set email alerts
|

Influences of yokukansankachimpihange on aggressive behavior of zinc-deficient mice and actions of the ingredients on excessive neural exocytosis in the hippocampus of zinc-deficient rats

Abstract: We examined the effect of Yokukansankachimpihange (YKSCH), a form of Yokukansan containing parts of two herbaceous plants, Citrus Unshiu Peel (Chimpi) and Pinellia Tuber (Hange), on aggressive behavior of mice housed individually. Mice were fed a zinc-deficient diet for 2 weeks. In a resident-intruder test, the cumulative duration of aggressive behavior was decreased in zinc-deficient mice administrated drinking water containing YKSCH (approximately 300 mg/kg body weight/day) for 2 weeks. We tested mice for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Tamano et al . also reported that geissoschizine methyl ether and 18 beta‐glycyrrhetinic acid, a major metabolite of glycyrrhizin contained in Glycyrrhiza, attenuated excess exocytosis at mossy fiber boutons induced by KCl in hippocampal slices from zinc‐deficient rats . Moreover, these compounds also attenuated the increase in intracellular Ca 2+ levels induced by KCl.…”
Section: Neuropharmacological Effectsmentioning
confidence: 85%
“…Tamano et al . also reported that geissoschizine methyl ether and 18 beta‐glycyrrhetinic acid, a major metabolite of glycyrrhizin contained in Glycyrrhiza, attenuated excess exocytosis at mossy fiber boutons induced by KCl in hippocampal slices from zinc‐deficient rats . Moreover, these compounds also attenuated the increase in intracellular Ca 2+ levels induced by KCl.…”
Section: Neuropharmacological Effectsmentioning
confidence: 85%
“…Administration of Yokukansankachimpihange, a potential herbal medicine for BPSD, to zinc-deficient mice also ameliorates social isolation-induced aggressive behavior. The two common ingredients ameliorate abnormal glutamatergic neuron activity in the hippocampus [ 100 ]. It is likely that zinc-deficient animals are models to assess the effect of drugs on behavioral abnormality, such as BPSD.…”
Section: Zinc Deficiency and Behavioral And Psychological Symptomsmentioning
confidence: 99%
“…Furthermore, YKSCH treatment prolongs the total sleeping time and tends to increase sleep efficacy based on polysomnography recordings in normal young healthy subjects (3). YKSCH treatment has also been reported to reduce memory impairment and BPSD-like behavior, such as hallucinations and aggressive behavior, in several rodent models (4)(5)(6)(7). Although some research using animal models have begun to elucidate the action of YKSCH in the central nervous system, little is known about how YKSCH alleviates insomnia observed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%